Collection management for the 21st century : a handbook for librarians - Gorman, G. E.; Miller, Ruth H. (The Greenwood library management collection, 1997)
Collection management is becoming increasingly complex due to electronic access to information, the growth of the Internet, greater reliance on document delivery and resource sharing, and changes in scholarly communication. This professional reference shows how changes in all aspects of collection management will affect future activities in this area and examines the likely value of these changes in the next century. Chapters are written by leading practitioners and academics from around the world, and the volume concludes with a bibliographical essay